Aplikasi Simulasi Tes Toefl Berbasis Android di Fakultas Keguruan dan Ilmu Pendidikan Universitas Hamzanwadi - Sa'dah, Sa'dah; Arianti, Baiq Desi Dwi (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
This study aims to develop and appropriateness discover of the Android-based TOEFL test simulation application at FKIP of Hamzanwadi UniversityÂ and discover the response of students to the Android-based TOEFL test simulation application at FKIP of Hamzanwadi University. This research is Research and Development with ADDIE development model. The results of this study are the Android-based TOEFL Test Simulation Application at FKIP of Hamzanwadi University, with the display in the form of a main menu page consisting of six navigation buttons: navigation structure material, listening material,Â  reading material, tips and trick, simulation test, and developer profile. The results of the media expert feasibility test are based on two aspects of assessment, namely the software engineering aspect and the display aspect are in the very feasible category with a total percentage of eligibility of 91%. And the results of the feasibility test from material experts are based on two aspects of assessment, namely the aspect of material content and language & communication, which is in the feasible category with a total percentage of eligibility of 79%. Meanwhile, based on student responses tested to 30 students on the developed application is positive with a total percentage of 78%.